The early-onset febrile reaction following vaccination and associated factors: An exploratory sub-study based on the Ebola vaccine clinical trial. Issue 6 (3rd June 2017) - Dai, Qigang; Liang, Qi; Hu, Yuemei; Meng, Fanyue; Li, Jingxin; Hou, Lihua; Zhou, Hailong; Chu, Kai; Hu, Xiaokui; Tang, Rong; Wang, Wenjuan; Hu, Jialei; et al.
ABSTRACT: A phase-1 clinical trial aimed to assess the safety and immunogenicity of the type-5 adenovirus vector based Ebola vaccine (Ad5-EBOV) was conducted in China. To provide more evidence for the safety evaluation and dose-selection, an exploratory sub-study using a wireless automatic temperature measuring platform was done based on the phase-1 clinical trial. The main aim of the sub-study was to obtain more information about the occurrence of fever and detect the potential associated factors, second was to assess the feasibility of the temperature measuring platform in vaccine clinical trials. Temperature data of 3 treatment groups all presented a rising tendency during the first 6 hours after vaccination, the incidence of elevated temperature and possible associated factors were analyzed. For the incidence of elevated temperature, no marked dose-response relationship was found in 6 hours with wireless thermometers; the information from mercury thermometers showed that the grade-1 fever proportion peaked at 6 hours and there was no difference between groups, while grade-2 fever proportion peaked at 24 hours and was significantly higher in high-dose group than those in the other 2 groups. Significant differences were found between sex groups (males vs. female, incidence rate ratios ( IRR ) = 2.93 and 7.62 for any-grade, grade-2 fever respectively, P<0.001); a decline in grade-2 fever incidence was found with the increasing age groups ( IRR = 0.78, P = 0.003) and body mass index (BMI, IRR = 0.67, P <0.001) .Our findings show that the dose-dependent manner between fever and the dose of Ad5-EBOV in this study might emerge after 6 hours, and which is slight and transient. Wireless thermometers secured on the skin surface are not suitable for a long time (longer than 6 hours) measurement, new methods for temperature monitoring, like ear temperature measurement, should be tested in the further research.